Possible seasonal and diurnal modulation of Gammarus pulex (Crustacea, Amphipoda) drift by microsporidian parasites - Sebastian Prati; Julian Enß; Daniel S. Grabner; Annabell Huesken; Christian K. Feld; Annemie Doliwa; Bernd Sures (Scientific Reports, 2023)
Abstract In lotic freshwater ecosystems, the drift or downstream movement of animals (e.g., macroinvertebrates) constitutes a key dispersal pathway, thus shaping ecological and evolutionary patterns. There is evidence that macroinvertebrate drift may be modulated by parasites. However, most studies on parasite modulation of host drifting behavior have focused on acanthocephalans, whereas other parasites, such as microsporidians, have been largely neglected. This study provides new insight into possible seasonal and diurnal modulation of amphipod (Crustacea: Gammaridae) drift by microsporidian parasites. Three 72 h drift experiments were deployed in a German lowland stream in October 2021, April, and July 2022. The prevalence and composition of ten microsporidian parasites in Gammarus pulex clade E varied seasonally, diurnally, and between drifting and stationary specimens of G. pulex. Prevalence was generally higher in drifting amphipods than in stationary ones, mainly due to differences in host size. However, for two parasites, the prevalence in drift samples was highest during daytime suggesting changes in host phototaxis likely related to the parasite’s mode of transmission and site of infection. Alterations in drifting behavior may have important implications for G. pulex population dynamics and microsporidians’ dispersal. The underlying mechanisms are more complex than previously thought.